Role of Extracellular Vesicles in the Pathogenesis of Venous Thromboembolism - Jamaly, Simin (UiT The Arctic University of Norway, 2018)
The papers I-IV are not available in Munin. Paper I: Jamaly, S., Basavaraj, M.G., Starikova, I., Olsen, R., Brækkan, S.K. & Hansen, J.B. Elevated Plasma Levels of P-Selectin Glycoprotein Ligand-1 (PSGL-1) Positive Microvesicles in Patients with Unprovoked Venous Thromboembolism. (Manuscript). Paper II: Jamaly, S., Ramberg, C., Olsen, R., Latysheva, N., Webster, P., Sovershaev, T. & Hansen, J.B. Impact of preanalytical conditions on plasma concentration and size distribution of extra cellular vesicles using Nanoparticle Tracking Analysis. (Manuscript). Paper III: Starikova, I., Jamaly, S., Sorrentino, A., Blondal, T., Latysheva, N., Sovershaev, M. & Hansen, J.B. (2015). Differential expression of plasma miRNAs in patients with unprovoked venous thromboembolism and healthy control individuals. Available in Thrombosis Research, 136(3), 566-72. Paper IV: Ramberg, C., Jamaly, S., Latysheva, N., Wilsgaard, L., Basavaraj, M.G., Sovershaev, T. & Hansen, J.B. A readily and robust assay to measure levels of procoagulant (P) activity of negatively charged phospholipids (PL)-a modified clot-based PPL assay. (Manuscript). Venous thromboembolism (VTE) is a common disease with an incidence of 1–2 per 1000 individuals. VTE is a collective term for deep vein thrombosis and pulmonary embolism. Extracellular vesicles (EVs) are lipid-membrane-bound spherical vesicles that bud off from the cells upon activation and apoptosis. Their size varies between 30 nm and 1 μm. Recent advances in experimental and observational studies suggest a pivotal role of EVs in VTE. The main goals of the present thesis were to assess plasma levels, the cellular origin and the morphological characteristics of P-selectin Glycoprotein Ligand-1 (PSGL-1) positive microvesicles (MVs) in patients with unprovoked VTE. We investigated the potential of microRNA (miRNA) plasma levels as biomarkers for unprovoked VTE, as well as the impact of pre-analyses handling and fasting status on plasma EVs. We also developed a cost-effective modified assay ...